Pengaruh Model Pembelajaran Berbasis Masalah dengan Metode Eksperimen Terhadap Hasil Belajar Fisika Siswa Kelas X SMAN 1 Gunungsari Kabupaten Lombok Barat Tahun Pelajaran 2014/2015 - Azmi Aziz; Joni Rokhmat; Kosim Kosim (Department of Physics Education, Universitas Mataram, 2015)
This research aims to find out the effect of problem based learning model with eksperiment method on the studentÃ¢â¬â¢s results of learning physics of grade X SMAN 1 Gunungsari regency west Lombok in academic year 2014/2015. This research is a quasi eksperiment with pretest posttest control group design. The population of this research is students of grade X SMAN 1 Gunungsari, with cluster random sampling technique was obtained students of grade X5 as the experiment group and students of grade X2 as control group. The result of learning is analized by using t-test polled varians, was obtained 9,25 for thint and 1,99 for ttable with significant 5%. Because thint > ttable, then Ho will be rejected and Ha will be accepted. So can be concluded that available effect of problem based learning model with eksperiment method on the studentÃ¢â¬â¢s results of learning physics of grade X SMAN 1 Gunungsari regency west Lombok in academic year 2014/2015.